2016
DOI: 10.1017/s0021859616000356
|View full text |Cite
|
Sign up to set email alerts
|

Triticale out-performs wheat on range of UK soils with a similar nitrogen requirement

Abstract: SUMMARYTriticale has a reputation for performing well on poor soils, under drought and with reduced inputs, but there has been little investigation of its performance on the better yielding soils dominated by wheat production. The present paper reports 16 field experiments comparing wheat and triticale yield responses to nitrogen (N) fertilizer on high-yielding soils in the UK in harvest years 2009–2014. Each experiment included at least two wheat and at least two triticale varieties, grown at five or six N fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
7
14
0
Order By: Relevance
“…This could be explained by our assumptions about optimum agronomic management practices for effectively meeting N demand and achieving effective biological controls for any weed, disease and pest infestations, factors that generally reduce farmers’ as well as the national yields. However, mean current wheat yields of the present study are close to good year wheat yields (8–14 t ha −1 ) as reported by various studies across the UK and NZ 42,59,61,63,64 . Management optimal wheat yield potentials had been estimated and reported in the range of 7–13 t ha −1 in the north-western Europe including the UK mainly due to favourable climatic conditions and adapted local cultivars 15,19 .…”
Section: Resultssupporting
confidence: 87%
“…This could be explained by our assumptions about optimum agronomic management practices for effectively meeting N demand and achieving effective biological controls for any weed, disease and pest infestations, factors that generally reduce farmers’ as well as the national yields. However, mean current wheat yields of the present study are close to good year wheat yields (8–14 t ha −1 ) as reported by various studies across the UK and NZ 42,59,61,63,64 . Management optimal wheat yield potentials had been estimated and reported in the range of 7–13 t ha −1 in the north-western Europe including the UK mainly due to favourable climatic conditions and adapted local cultivars 15,19 .…”
Section: Resultssupporting
confidence: 87%
“…This could be explained by our assumptions about agronomic management practices that are effective in meeting the N demand and achieving full control of any weed, disease and pest infestations, factors that may reduce the national mean wheat yield. The mean baseline wheat yields in the present study are close to good year wheat yields (8–14 t ha -1 ) as reported by various studies across the UK and NZ ( Carmo-Silva et al, 2017 ; Craigie et al, 2015 ; Curtin et al, 2008 ; Perryman et al, 2018 ; Roques et al, 2017 ). Different studies reported similar yield potentials of current wheat cultivars under optimal managements in high productive countries at high latitude ( Boogaard et al, 2013 ; Schils et al, 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…The environmental index is a valuable tool for discriminating cultivars with augmented tolerance to drought stress (Sio-Se Mardeh et al, 2006), but also for genotypes of high yield potential in more favorable environments, like triticale in our study. The higher yield potential of triticale in high yielding environments has also been recorded in 16 sites in the United Kingdom, where the average GY of two triticale cultivars (8.27 and 9.01 t ha -1 ) was higher compared to two wheat cultivars (7.26 and 7.94 t ha -1 ) (Roques et al, 2017). Other studies comparing triticale and durum wheat in drought-prone Mediterranean environments (Australia, Spain, Sardinia, Lebanon, and Tunisia), also revealed the higher GY of triticale (Giunta et al, 1993; López-Castañeda and Richards, 1994; Villegas et al, 2010).…”
Section: Discussionmentioning
confidence: 67%
“…Indeed, field trials conducted in Australia, Spain, Sardinia, Lebanon and Tunisia, have shown that triticale yields tend to be greater than bread or durum wheat (Giunta et al, 1993; López-Castañeda and Richards, 1994; Villegas et al, 2010). In the high-yielding environments of the United Kingdom, the average GY of triticale cultivars was also larger than wheat cultivars (Roques et al, 2017).…”
Section: Introductionmentioning
confidence: 99%